SYNTHESIS OF Co(II)-TiO2/KAOLINITE AS A ANTIBACTERIAL Escherichia coli PHOTOCSINTESIS Co(II)-TiO2/KAOLIN SEBAGAI FOTOKATALIS ANTIBAKTERI Escherichia coli DENGAN BANTUAN SINAR TAMPAK (SYNTHESIS OF Co(II)-TiO2/KAOLINITE AS A ANTIBACTERIAL Escherichia coli PHOTOCATALYST UNDER VISIBLE LIGHT) - Elyta Clarissa; Adhitiyawarman Adhitiyawarman; Anthoni B Aritonang (Indonesian Journal of Pure and Applied Chemistry, 2021)
Photocatalyst Co(II)-TiO2/kaolinite as a antibacterial E.coli has been successfully synthesized using sol-gel method. The purpose of this study was to determine the characteristics and Co(II)-TiO2/kaolinite photocatalyst activity as antibacterial E.coli under visible light. Synthesis of Co(II)-TiO2/kaolinite using TTIP as a precursor for Ti and CoCl2.6H2O as a precursor to Co(II) dopant. The doping process is carried out using the sol-gel method with the stages of hydrolysis, condensation, aging and calcination at a temperature of 450 ºC. The impregnation process on kaolinite was carried out using the wet impregnation method. The antibacterial activity test of E.coli under visible light was carried out using the turbidimetric method using a UV-Vis spectrophotometer at a wavelength of 600 nm. The activity test results showed that the Co(II)-TiO2 photocatalyst with a concentration of Co(II) dopant 3 %w/v had the best inhibition power reaching 35,47 %. The synthesized Co(II)-TiO2/kaolinite photocatalyst was analyzed using FTIR, XRD and UV-Vis DRS instruments. The results of FTIR analysis show that there is a shift in Ti-O absorption towards a smaller wave number which indicates that the Co(II) dopant has successfully entered the TiO2 structure. The XRD diffractogram showed that the Co(II)-TiO2/kaolinite photocatalyst had an anatse phase at 2q = 25,256º with a crystal size of 17-25 nm. UV-Vis DRS spectroscopic analysis showed a decrease in the band gap energy value from 3.35 eV to 1.69 eV.